Text-fig. 2. a, b: Pinus aff. peuce cones. a: Oriolo, MSF 643. b: Tebano, MSF 1021. c: Abies aff. alba cone scale, Oriolo MSF 988. d, e: Tsuga chiarugii cones. d: Oriolo MSF 638. e: Oriolo MSF 979. f, h: Bambusa lugdunensis leaves and leafy axis. f: Oriolo MSF 937. h: Oriolo MSF 651. g: Modern leaf of Yushania for comparison (NMNS Cleared Leaf Database specimen U1347). i: Phragmites sp. Oriolo MSF n.n. Scale bars 50 mm (a, b, h, i), 10 mm (c–g). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 2. a, b: Pinus aff. peuce cones. a: Oriolo, MSF 643. b: Tebano, MSF 1021. c: Abies aff. alba cone scale, Oriolo MSF 988. d, e: Tsuga chiarugii cones. d: Oriolo MSF 638. e: Oriolo MSF 979. f, h: Bambusa lugdunensis leaves and leafy axis. f: Oriolo MSF 937. h: Oriolo MSF 651. g: Modern leaf of Yushania for comparison (NMNS Cleared Leaf Database specimen U1347). i: Phragmites sp. Oriolo MSF n.n. Scale bars 50 mm (a, b, h, i), 10 mm (c–g). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 222, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867